Importance of Communicative English for the Readers: Enhancing Business Success through Communicative English (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Communication has always been important not only in man’s life but also in the life of various living species. Man needs to communicate to express various needs feelings and emotions. He needs communication for the fulfillment of his emotional needs. Prof. A.P. Girdhar writes that the art of effective communication is very important in man’s personal life. It has the ability to set itself free from geographical environments. With the advent of multinationals, with the modernization of business techniques, effective communication has acquired greater importance .The process of communication may be as old as the world itself but the rapid technological and scientific development of the world has enormously increased the importance of effective communication system. Communicating with others is a part of everyday life. In large part, communication is about explicit language speaking and writing words but communication is also about implicit messages, such as tone, or eye contact. In recent years the importance of professional communication has increased manifold. This is because of growing complexity in organizational behavior. There has been rapid industrial growth and great advance in business management techniques. There is also the impact of modern technology on professional communication. This is because of growing complexity communication techniques have to meet the demands of fast changing business words. There is content need for review and modification of professional communication system. There is constantly growing realization by the professionals about the importance of professional communication. To meet the challenges of rapid industrial growth and globalization business houses are giving greater attention to professional communication techniques. The ability to communicate effectively has become Key to success of a business venture. The present paper is an attempt to attract the attention of the readers towards the importance of Communicative English.